ROAD GEOMETRIC PLANNING USING AUTOCAD®2D CASE STUDY: PRAPATAN PANJALIN STREET, SUMBERJAYA DISTRICT, MAJALENGKA REGENCY - Indra Pernama; Andri Irfan Rifa'i; Adinda Fajarika (Fakultas Teknik Sipil dan Perencanaan, 2024)
Jalan Prapatan Panjalin is a road located in Sumberjaya sub-district, Majalengka district, which is a connecting road between Sumberjaya sub-district and Palasah sub-district, which has a road length of around 7 km. Besides that, the Panjalin Prapatan road is classified as an arterial class I road. In this study, it refers to the geometric roads issued by the Ministry of Public Works and Public Housing in 2020, the Director General of Highways. And the design results are visualized using AutoCAD 2D. for a predetermined design speed of 60 km/hour with a radius of 112 m. and elevation (e max ) which is 10% , based on these design criteria, obtained a circular arc length ( Lc ) of 249.884 m. then formed by vertical alignment Long ppv (L) of a kind of concave curve.